IMPLEMENTASI SISTEM INFORMASI AKUNTANSI, SISTEM PENGUKURAN KINERJA TERHADAP KINERJA MANAJERIAL PADA KOPERASI SIMPAN PINJAM - Murti, I Wayan Indra Wiguna (Institut Agama Hindu Negeri Gde Pudja Mataram, 2023)
Technology is advancing at an ever-increasing rate these days, and accounting computation processes in businesses are no exception. Performance evaluation and accounting information systems are crucial components of managerial effectiveness in businesses. This is why the purpose of this study is to evaluate the accounting information system and the performance evaluation system in Mataram City's savings and loan cooperatives.